Inhibition of let-7 augments the recruitment of epicardial cells and improves cardiac function after myocardial infarction. (May 2016) - Seeger, Timon; Xu, Quan-Fu; Muhly-Reinholz, Marion; Fischer, Ariane; Kremp, Eva-Maria; Zeiher, Andreas M.; Dimmeler, Stefanie
Abstract: Heart failure due to myocardial infarction is a major cause of mortality. The microRNA (miR) family let-7 is expressed during embryonic development and is up-regulated in differentiated cells. The aim of this study was to study the role of let-7 after acute myocardial infarction (AMI). We designed an antimiR to inhibit the highest expressed members of the let-7 family, let-7 a, b and c. Administration at day 0 and day 2 after AMI resulted in sustained knockdown of let-7 after 28 days. Let-7 inhibition prevented deterioration of cardiac functions compared to control treatment which was especially due to improvements in the infarcted, apical cardiac segments. We observed higher contents of fibrosis in the border zone as well as increased numbers of cells positive for TCF21, which is also expressed in epicardial cells. Markers were augmented after let-7 inhibition and let-7 blocked EMT in epicardial cells in vitro. Lineage tracing in TCF21 iCre/+ :R26R tdT mice showed abundant tomato positive cells in the infarct and border zone. In conclusion, let-7 inhibition resulted in functional benefits due to an increase in recruitment of epicardial cells and EMT. Highlights: Inhibition of let-7 prevents deterioration of cardiac function after acute myocardial infarction. Increase in function is based on a positive remodeling in particular of the apical regions. Inhibition of let-7 results in an increased recruitment of epicardial cells in the border zone. Let-7 inhibition enhances epithelial- to mesenchymal transition in epicardial cells.